Pengenalan Perancangan Kapal Phinisi Melalui Filosofi Budaya Bugis Makassar dan Al-Qur’an di Madrasah Tahfidz Al-Qur’an Addalawiyah, Thailand Selatan - Dirgahayu Lantara; Nurul Chairany; Muhammad Budi Adiputra Reski (Pusat Riset dan Inovasi Nasional, 2026)
The disconnection in the transmission of maritime knowledge to partners in Southern Thailand poses a serious challenge to the preservation of cultural identity. The activity partner, Madrasah Tahfidz Al-Qur’an Addalawiyah in Pattani, faces obstacles in contextualizing its revelation based curriculum with modern technological advancements. This community service program aims to bridge this gap through an ethno techno religious approach. The implementation employs the Participatory Action Learning (PAL) method, which integrates the philosophy of Phinisi shipbuilding, Critical Path Method (CPM) project management, and the interpretation of Kauniyah verses. Therefore, a structured process of introducing Bugis-Makassar culture through sharing sessions using storytelling and discussion methods is necessary. The results of the activity indicate that: (1) internalizing the values of Siri’ na Pacce in ship construction can awaken students’ collective memory of their ancestral heritage; (2) the application of the PERT/CPM method in shipbuilding simulations provides a concrete understanding of time management aligned with Q.S. Al-‘Asr; and (3) the emergence of a new paradigm in which shipbuilding technology is understood as a tangible manifestation of the teachings of the Qur’an. This program recommends an integrative education model that positions local wisdom as the entry point for science learning in faith-based educational institutions